Mixed layer depth climatology over the northeast U.S. continental shelf (1993–2018). (1st December 2021) - Cai, Cassia; Kwon, Young-Oh; Chen, Zhuomin; Fratantoni, Paula
Abstract: The Northeast U.S. (NEUS) continental shelf has experienced rapid warming in recent decades. Over the NEUS continental shelf, the circulation and annual cycle of heating and cooling lead to local variability of water properties. The mixed layer depth (MLD) is a key factor that determines the amount of upper ocean warming. A detailed description of the MLD, particularly its seasonal cycle and spatial patterns, has not been developed for the NEUS continental shelf. We compute the MLD using an observational dataset from the Northeast Fisheries Science Center hydrographic monitoring program. The MLD exhibits clear seasonal cycles across five eco-regions on the NEUS continental shelf, with maxima in January–March and minima in July or August. The seasonal cycle is largest in the western Gulf of Maine (71.9 ± 24.4 m), and smallest in the southern Mid-Atlantic Bight (34.0 ± 7.3 m). Spatial variations are seasonally dependent, with greatest homogeneity in summer. Interannual variability dominates long-term linear trends in most regions and seasons. To evaluate the sensitivity of our results, we compare the MLDs calculated using a 0.03 kg/m 3 density threshold with those using a 0.2 °C temperature threshold. Temperature-based MLDs are generally consistent with density-based MLDs, although a small number of temperature-based MLDs are biased deep compared to density-based MLDs particularly in spring and fall. Finally, we compare observational MLDs to the MLDs from a high-resolution ocean reanalysis GLORYS12V1. While the mean values of GLORYS12V1 MLDs compare well with the observed MLDs, their interannual variability are not highly correlated, particularly in summer. These results can be a starting point for future studies on the drivers of temporal and spatial MLD variability on the NEUS continental shelf. Highlights: First MLD seasonal climatology for the entire Northeast U.S. Continental Shelf. 38, 340 hydrography from the Northeast Fisheries Science Center is analyzed. State-of-the-art ocean reanalysis is evaluated against the new MLD climatology.